Communications in Statistics: Simulation and Computation - Marcel Dekker (New York Marcel Dekker, 1976)
Print + Online (1997-)
Some issues also have distinctive titles.
Keywords: Mathematical statistics -- Periodicals; Mathematical statistics -- Data processing -- Periodicals; Digital computer simulation -- Periodicals